Does a Local B‐Minimum Appear in the Tail Current Sheet During a Substorm Growth Phase? - V. A. Sergeev; E. I. Gordeev; V. G. Merkin; M. I. Sitnov (Geophysical Research Letters)
Abstract Magnetic configurations with dBz/dr > 0 in the midtail current sheet are potentially unstable to various instabilities associated with the explosive substorm onset. Their existence is hard to confirm with observations of magnetospheric spacecraft. Here we use remote sensing by low‐altitude spacecraft that measured the loss cone filling rate during electron‐rich solar particle event, providing information about magnetic properties of the tail current sheet. We found a latitudinally localized anisotropic 30 keV electron loss cone region embedded inside an extended region of isotropic solar electron precipitation. It was persistently observed for more than 0.5 h during isolated growth phase event by six Polar Operational Environmental Satellites spacecraft, which crossed the premidnight auroral oval. The embedded anisotropic region was observed 1° poleward of the outer radiation belt boundary over 4–5 h wide magnetic local time sector, suggesting a persistent ridge‐type Bz2/j maximum in the equatorial plasma sheet at distances 15–20 RE. We discuss infrequent observations of such events taking into account recent results of global magnetohydrodynamic simulations.